Charalambides, Alexandros G. - (:unkn) unknown (My University, 2026)
Dr Alexandros Charalambides is a Mechanical Engineering graduate and holds a PhD from Imperial College London. His PhD project was funded by Honda R & D Co, Ltd of Japan. He has worked at Imperial College London, at the University of Tokyo and on his return to Cyprus, at the Energy Service of the Ministry of Commerce, Industry and Tourism. In 2009, he was appointed a Lecturer in the Department of Environmental Science and Technology of the Cyprus University of Technology. His research interests are focused on experimental fluid dynamics and their adaptation to non-traditional energy systems, as well as on the creation of a proper policy in Cyprus for tackling climate change. In particular he is working on: Conducting studies on energy saving measures and on the use of renewable energy. Improving Homogeneous Charge Compression Ignition Engines. Energy production from swine waste using algae. The impact of local weather conditions on solar energy
Keywords: energy; environmental